2005
DOI: 10.2165/00024677-200504020-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dehydroepiandrosterone Therapy in Clinical Practice

Abstract: Dehydroepiandrosterone (DHEA) therapy is controversial due to sensationalized reports of epidemiologic studies and the over-the-counter availability of DHEA. Human clinical trials have investigated the potential efficacy of DHEA therapy in multiple conditions with resultant inconsistencies in findings. DHEA is unique compared with other adrenal steroids because of the fluctuation in serum levels found from birth into advancing age. The lower endogenous levels of DHEA and DHEA sulfate found in advancing age hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 163 publications
1
13
0
Order By: Relevance
“…Wolkowitz et al only reported that DHEA treatment had significant beneficial effects on depressive symptoms in patients with major depression (77). Cameron et al suggested that doses of 30 to 50 mg of oral DHEA produce physiological androgen levels and that 50 mg of DHEA increases serum androgen levels within the physiological range as well as possible improvements of sexual function and mood and decrease in fatigue/exhaustion in women (78). A recent study has revealed that intravaginal administration of DHEA can be used to treat vaginal atrophy (79).…”
Section: Supplementation Of Testosterone and Dhea-s In Womenmentioning
confidence: 99%
“…Wolkowitz et al only reported that DHEA treatment had significant beneficial effects on depressive symptoms in patients with major depression (77). Cameron et al suggested that doses of 30 to 50 mg of oral DHEA produce physiological androgen levels and that 50 mg of DHEA increases serum androgen levels within the physiological range as well as possible improvements of sexual function and mood and decrease in fatigue/exhaustion in women (78). A recent study has revealed that intravaginal administration of DHEA can be used to treat vaginal atrophy (79).…”
Section: Supplementation Of Testosterone and Dhea-s In Womenmentioning
confidence: 99%
“…lipid metabolism, atherosclerosis, osteoporosis [16][17][18][19][20]. Moreover, it has been demonstrated that DHEA treatment can improve mood, well-being, sexual functions and cognition in young adults with primary and secondary adrenal insufficiency [21,22]. Pharmacodynamic studies suggest that daily doses of 30-50 mg of oral DHEA may produce physiologic hormone levels [22].…”
Section: Introductionmentioning
confidence: 99%
“…More detailed studies have been performed in recent years to evaluate the potential role of androgen in the prevention/cure of autoimmune diseases like SLE, with results that generally suggest that androgens are responsible for the protection against autoimmune disease. In some of such studies the role of testosterone in the treatment of SLE was emphasized, wherein the administration of various forms of the steroid alleviated SLE, or SLE development was seen to occur if levels of testosterone dropped (87,117,(153)(154)(155). In the Lupus prone NZB x NZW mice, more suppressor cells were generated in the presence of testosterone, suggesting their role in protecting susceptible mouse strains from the production of autoantibodies (156).…”
Section: Cd28/b7-1/b7-2/ctla-4 and Regulatory T Cellsmentioning
confidence: 99%
“…In some of such studies the role of testosterone in the treatment of SLE was emphasized, wherein the administration of various forms of the steroid alleviated or modified the course of SLE in both females and males (87,117,(153)(154)(155)188). a).…”
Section: Estrusmentioning
confidence: 99%
See 1 more Smart Citation